A Description Of Adolescent Girls' Behavior Regarding Personal Hygiene When Experiencing Vaginal Discharge At MAN 1 Surakarta - Anggun Herawati; ⁠Irma Mustika Sari (CV. AFDIFAL MAJU BERKAH, 2026)
Adolescence is susceptible to vaginal discharge due to hormonal changes and tropical climate, with a prevalence of 75% in Indonesia and low knowledge in Central Java. This study aims to describe the personal hygiene behavior of adolescent girls during vaginal discharge at MAN 1 Surakarta. The quantitative descriptive method with stratified random sampling resulted in a sample of 89 female students from a population of 773 female students in grades X-XII. The 24-item Likert questionnaire instrument was analyzed univariately using SPSS for frequencies and percentages. The results showed that 89.9% of respondents aged 14-17 years, 100% had a history of vaginal discharge, 85.4% used social media as their information source, and 55.1% had sufficient behavior and 44.9% good behavior. It was concluded that the majority of adolescent girls have sufficient personal hygiene behavior, requiring social media-based educational intervention.